On the Illegality of Sex Work and the Impact on Victimization, Health, and Human Trafficking: Is Criminalization a Cure or Disease? - Burckley, Jacquelyn (Victims & offenders, 2023)
Despite the apparent ubiquity of prostitution over time and place, and legality of most other modern forms of sex work (e.g., erotic dancing, cam girls, entrepreneurial pornography), prostitution remains criminalized around most of the globe. In recent years there has been a push to reevaluate this stance, with new debates arising over the positive and negative implications of criminalizing prostitution, with particular attention paid to victimization, public health, and human trafficking. Still, most of these arguments are emotive, political, or normative in nature, and rarely are empirical evaluations of the impact of criminalized prostitution included in this narrative. This essay aims to address this issue by presenting the scientific findings on the impact of criminalized prostitution with respect to violence/victimization, public health, and risk of sex trafficking. We find that overall, criminalization has iatrogenic effects on victimization and public health (such as spread of STDs, use of condoms, etc.) in the literature, but the impact on sex trafficking is more mixed. We therefore call for more research and funding to be dedicated to the issue, with focus on developing and evaluating policies that specifically aim to maximize benefits from decriminalizing prostitution across domains, while also protecting our most vulnerable.